2016
DOI: 10.1080/2162402x.2016.1254854
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic RORγ agonists regulate multiple pathways to enhance antitumor immunity

Abstract: RORγt is the key transcription factor controlling the development and function of CD4+ Th17 and CD8+ Tc17 cells. Across a range of human tumors, about 15% of the CD4+ T cell fraction in tumor-infiltrating lymphocytes are RORγ+ cells. To evaluate the role of RORγ in antitumor immunity, we have identified synthetic, small molecule agonists that selectively activate RORγ to a greater extent than the endogenous agonist desmosterol. These RORγ agonists enhance effector function of Type 17 cells by increasing the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
112
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 46 publications
(42 reference statements)
3
112
0
Order By: Relevance
“…1B). Consistent with the findings in mouse T cells (11), this in vitro agonist treatment induced the cells to produce 6-fold more IL17A without compromising their ability to produce IFNγ (Fig. 1C and D).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…1B). Consistent with the findings in mouse T cells (11), this in vitro agonist treatment induced the cells to produce 6-fold more IL17A without compromising their ability to produce IFNγ (Fig. 1C and D).…”
Section: Resultssupporting
confidence: 89%
“…We reported that a series of RORγ agonists could augment the effector function of murine Type 17 T cells in vitro and improve their antitumor activity when administered as an oral therapy in mice bearing syngeneic tumors (11). To extend these results and evaluate how RORγ agonists would affect human chimeric antigen receptor (CAR) T cells, human total T (CD4 + and CD8 + ) cells were enriched from the peripheral blood of healthy individuals, programmed using Type 17 polarizing conditions (IL1β, IL6, IL23), activated with anti-CD3/CD28 beads and 1 day after activation, transduced with a lentiviral vector that encodes a CAR recognizing mesothelin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations